Resourceful Power Aware Routing Protocol in MANET (International Journal of Engineering and Computer Science, 2015)
Power saving is an important factor in Mobile Ad hoc Networks, because most of the equipment in MANETs are battery powered. So we have to reduce the power consumption of each and every node. There are several methods to reduce the power consumption of nodes. An effective method is sending the packets with optimum power. In this paper, we propose an energy efficient power aware routing (EPAR) protocol, a new power aware routing protocol. The objective of the proposed protocol is to increase the service lifetime of MANET with dynamic topology. Basically, EPAR is an improvement of DSR (Dynamic Source Routing) protocol. In EPAR path is chosen based on hop count and mobility in addition to energy unlike DSR where path is chosen based only on minimum number of hops. The proposed approach is a dynamic distributed, load balancing approach that avoids power-congested nodes and chooses paths that are lightly loaded. This helps the protocol to achieve minimum variance in energy levels of different nodes in the network and maximizes the network lifetime. This improves the throughput of our network and the main motivation is to reduce the power consumption of each and every network.